Relentless expansion of a lifestyle café? / Seri Ayu Masuri Md Daud ... [et al.] - Md Daud, Seri Ayu Masuri; Jusoh, Fatmawati; Sulaiman, Saliza; Yeop Johari, Halim Suhaimi; Zainal Abidin, Adnan (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
This case study is about a lifestyle café that originated during a date with the entrepreneur's fiancée and built by the endurance, smarts, and sweat of two brothers. The brothers named the café Brotherhood & Co. (Brotherhood) to represent the spirit of togetherness created between them while building their café. Founded in 2015, Brotherhood has been steadily expanding over the past five years. Known for its creative and captivating menus, Brotherhood is incredibly popular among youths. A food blog post that went viral in the first six months of Brotherhood's inception made it a breeze for the café to double its daily sales to over RM10,000. Recently, however, customers began to change their preferences to ordering food using their cell phones. Besides, the movement control order caused by the COVID-19 outbreak exponentially increased the demand for online food ordering for all restaurants. With the lifestyle café's dinein demand remains high, the brothers began grappling with the first significant expansion of their café. They viewed the shift in customer demand as a threat to their lifestyle café because they lacked the human and physical resources required to keep up with the exponential total demand growth due to the rapid development of online food delivery services. Faced with the unexpected threat that caused a significant loss in potential sales and combined with their inexperience as business managers, the brothers were unsure whether they should risk expanding the business and how rapidly they should do so how much they should invest. In particular, they confronted several difficult strategic choices: should they step up Brotherhood's growth trajectory to meet customer demand for online ordering services or forego the potential revenues increase and remain as the lifestyle café they originally envisioned? Their strategic decision involves several significant operational challenges: how to minimize dependency on cooks, how to deal with the erratic supply of halal chickens, and how to develop effective and efficient kitchen space that includes an advanced inventory management system and a large chiller. Even if they decide to invest in expanding their café, which online delivery method should they choose? Finally, a daunting question concerns COVID-19: will markets return to normal after a COVID-19 vaccine?